Innovation activity of firms in the Philippines - Francis Mark A. Quimba; Jose Ramon G. Albert; Gilberto M. Llanto (Philippine Institute for Development Studies (PIDS), 2017)
Set against a rapidly changing global environment, Philippine industries now, more than ever, are facing new demands that will require more innovation for firms to remain competitive across the global market. The PIDS Survey on Innovation Activities (PSIA) conducted among firms in food manufacturing, other manufacturing, ICT, and BPO suggests that in 2015, about 43% of Philippines establishments were innovation-active. Strikingly, the BPO sector spends the most for innovation activities despite it being the least innovation-active among the various sectors at a rate of just 30%. Intellectual property applications have been very low across all industries following firms' tendency to view their product innovations as trade secrets in order to maintain their competitive edge against rivals. The study also finds that the conduct of knowledge management activities is positively correlated with firm size. Moreover, larger firms tend to rely on internal sources for their information and innovation which is the case with the food processing and automotive sectors. Results of the panel data model explaining innovative behavior among 2015 PSIA firms, that were also part of a pilot survey in 2009, showed that knowledge management activities and firm size are adequate determinants of innovation behavior. Taking all these survey results into perspective, a national policy that is grounded on consultations with all stakeholders in the innovation ecosystem should be pursued. Enabling the business environment through stronger intellectual property rights can also encourage more firms to innovate especially among wary multinational companies.
Keywords: 330; innovation; product innovation; process innovation; innovation; micro; small and medium enterprises; industry-academe collaboration